2012
DOI: 10.1016/j.molonc.2012.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of inflammatory cytokines in primary cell culture in endometrial carcinoma

Abstract: Endometrial cancer is the most common malignancy of the female genital tract, and the incidence and mortality rates from this disease are increasing. Although endometrial carcinoma has been regarded as a tissue-specific disease mediated by female sex steroid pathways, considerable evidence implicates a role for an inflammatory response in the development and propagation of endometrial cancer. We hypothesized that if specific patterns of cytokine expression were found to be predictive of adverse outcome, then s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 46 publications
4
29
0
1
Order By: Relevance
“…Further extending the current knowledge on the complex regulation of VEGF, our data suggest that GPER may contribute to the HIF-1α mediated transcriptional responses in hypoxic tumor microenvironment towards new blood vessel formation. Notably, an increased VEGF production was recently shown to parallel an elevated GPER expression in endometrial cancer patients with low survival rates [61]. These data in combination with our findings may suggest that in estrogen-dependent cancer cells diverse molecular mechanisms could converge on the production of cytokines and growth factors, promoting an enhancement of malignant epithelial growth and invasion through autocrine and/or paracrine pathways.…”
Section: Discussionsupporting
confidence: 78%
“…Further extending the current knowledge on the complex regulation of VEGF, our data suggest that GPER may contribute to the HIF-1α mediated transcriptional responses in hypoxic tumor microenvironment towards new blood vessel formation. Notably, an increased VEGF production was recently shown to parallel an elevated GPER expression in endometrial cancer patients with low survival rates [61]. These data in combination with our findings may suggest that in estrogen-dependent cancer cells diverse molecular mechanisms could converge on the production of cytokines and growth factors, promoting an enhancement of malignant epithelial growth and invasion through autocrine and/or paracrine pathways.…”
Section: Discussionsupporting
confidence: 78%
“…High CSF1 concentrations in tumors are associated with poor prognosis and expression is often found at the leading edge of tumors (Laoui et al, 2011; Qian and Pollard, 2010). In endometrial cancer its synthesis by tumor cells is an independent predictor of poor overall survival (Smith et al, 2013). Consistent with these clinical observations, deletion of CSF1 genetically from several models of cancer results in delayed initiation (cervical), progression (breast, pancreas) and metastasis (breast) associated with the loss of TAMs.…”
Section: Macrophages In the Primary Tumormentioning
confidence: 99%
“…Interestingly, our data may recall previous findings showing that the ER antagonist and GPER agonist OHT (4, 7) is able to upregulate VEGF in different tumor types, including breast cancer (40,41). In addition, it has been recently reported that low survival rates in patients with endometrial cancer are associated with both elevated GPER expression and VEGF levels (42), further providing a relationship between these 2 main players of tumor cells and the surrounding stroma.…”
Section: Discussionmentioning
confidence: 97%